EISCAT_3D - a next-generation European radar system for upper atmosphere and geospace research - Wannberg, Gudmund; Eliasson, L.; Johansson, J.; Wolf, I.; Andersson, H.; Bergqvist, Peter; Häggström, I.; Iinatti, T.; Laakso, T.; Larsen, R.; Markkanen, J.; Marttala, I.; et al. (Luleå tekniska universitet, EISLAB, 2010)
The EISCAT Scientifi c Association, together with a number of collaborating institutions, has recently completed a feasibility and design study for an enhanced performance research radar facility to replace the existing EISCAT UHF and VHF systems. This study was supported by EU Sixth-Framework funding. The new radar retains the powerful multi-static geometry of the EISCAT UHF, but will employ phased arrays, direct-sampling receivers, and digital beamforming and beam steering. Design goals include, inter alia, a tenfold improvement in temporal and spatial resolution, an extension of the instantaneous measurement of full-vector ionospheric drift velocities from a single point to the entire altitude range of the radar, and an imaging capability to resolve small-scale structures. Prototype receivers and beamformers are currently being tested on a 48-element, 224 MHz array (the "Demonstrator") erected at the Kiruna EISCAT site, using the EISCAT VHF transmitter as an illuminator. Validerad; 2010; 20090807 (gustav_j)